Stakeholder management practices in Social Impact Assessment (SIA) of projects: a case of the Tema Motorway-Interchange Project in the Tema Metropolis - Osei, Patrick Yaw (2021)
A thesis submitted to the department of Construction Technology and Management, College of Art and Built Environment in partial fulfillment of the requirements for the award degree of Master of Science in Project Management.